2003
DOI: 10.1074/jbc.m304582200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement of SWI/SNF for Androgen Receptor Activity

Abstract: The androgen receptor (AR) is a ligand-dependent transcription factor whose activity is required for prostate cancer proliferation. Because ablation of AR activity is a critical goal of prostate cancer therapy, much emphasis has been placed on understanding the accessory proteins that regulate AR function in the prostate. Several co-activators have been shown to be required for full AR activity, including histone acetyltransferases and TRAP/mediator complexes. SWI/SNF comprises a family of large, multisubunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 68 publications
8
84
1
2
Order By: Relevance
“…The oncogenic transcription heterodimer activated protein-1 (AP-1) is known to be SWI/SNF dependent ; similarly, EKLF, which regulates b-hemogloblin synthesis, also requires this complex for its function (Armstrong et al, 1998;Lee et al, 1999). All known steroid receptors are functionally linked to SWI/SNF (Yoshinaga et al, 1992;Sumi-Ichinose et al, 1997;Fryer and Archer, 1998;Belandia et al, 2002;Inoue et al, 2002;Marshall et al, 2003;Flajollet et al, 2007). SWI/SNF has been linked to CD44, CEACAM1, E-cadherin and various integrins (Liu et al, 2001;Hendricks et al, 2004;Hill et al, 2004).…”
Section: Composition Of the Swi/snf Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The oncogenic transcription heterodimer activated protein-1 (AP-1) is known to be SWI/SNF dependent ; similarly, EKLF, which regulates b-hemogloblin synthesis, also requires this complex for its function (Armstrong et al, 1998;Lee et al, 1999). All known steroid receptors are functionally linked to SWI/SNF (Yoshinaga et al, 1992;Sumi-Ichinose et al, 1997;Fryer and Archer, 1998;Belandia et al, 2002;Inoue et al, 2002;Marshall et al, 2003;Flajollet et al, 2007). SWI/SNF has been linked to CD44, CEACAM1, E-cadherin and various integrins (Liu et al, 2001;Hendricks et al, 2004;Hill et al, 2004).…”
Section: Composition Of the Swi/snf Complexesmentioning
confidence: 99%
“…Although it has not been investigated, the loss of BRG1 and BRM could very well underlie the resistance to glucocorticoids in hematopoietic malignancies such as myeloma, lymphoma and leukemia, as well as in lung cancer (Choi et al, 2001b;Ko et al, 2004;Pottier et al, 2007). The estrogen receptor is also functionally linked to the SWI/SNF complex Belandia et al, 2002), and the androgen receptor is also SWI/SNF dependent (Inoue et al, 2002;Marshall et al, 2003;Hong et al, 2005;Link et al, 2005;Dai et al, 2008). We have found that BRG1 and BRM are lost in human prostate cancer samples, suggesting that a loss of SWI/SNF function may play a role in the development of hormone-refractory prostate cancer.…”
Section: Brm and Brg1 Control The Expression Of Genes That Are Involvmentioning
confidence: 99%
“…4A). To analyze a larger spectrum of validated AR targets, cyclin D1b-mediated regulation of probasin (ARR2) and sex-limited protein (SLP) expression was assessed (33,34). As shown, SLP-HRE2-LUC inhibition was compromised in a manner comparable with the PSA promoter, resulting in a 2.2-fold increase in AR activity as compared with cyclin D1a (Fig.…”
Section: Cyclin D1b Regulates Transcription In a Manner Distinct Frommentioning
confidence: 99%
“…3 C and D). Identical conditions were used to assess cyclin D1b impact on the PSA-LUC reporter, which lacks the distal enhancer region and associated AREs (33). Again, cyclin D1b failed to repress AR activity to the capacity of cyclin D1a (Fig.…”
Section: Cyclin D1b Regulates Transcription In a Manner Distinct Frommentioning
confidence: 99%
“…BRG1 was also shown to be required for androgen receptor activation of mouse mammary tumor virus transcription (39). However, Brm-containing complexes have been reported to be preferred in androgen receptor-mediated transcriptional activation of prostate-specific antigen and probasin (40). In the absence of SWI/SNF activity, androgen receptor-dependent activation of prostate-specific antigen transcription could not be restored by BRG1 but was strongly activated by Brm (40).…”
Section: Discussionmentioning
confidence: 89%